Penguatan Industrialisasi dalam Investasi Berkelanjutan di Indonesia - Joseph Emiliano Junior; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In the era of globalization and increasingly fierce economic competition, industrialization has become the main pillar in efforts to increase a country's competitiveness and economic growth. In Indonesia, strengthening industrialization does not only aim to increase production and exports, but must also be directed at sustainable investment that pays attention to environmental, social and governance (ESG) aspects. This research aims to analyze the strategies and policies needed to strengthen industrialization within the framework of sustainable investment in Indonesia. Through a qualitative approach with policy analysis and case studies of key industries, it was found that the integration of sustainability principles in industry can increase efficiency, reduce environmental impacts, and provide broader social benefits. In addition, government support through appropriate regulations, fiscal incentives, and increasing human resource capacity are key factors in realizing sustainable industrialization. It is hoped that the results of this research can be a reference for policy makers, industry players and investors in designing and implementing investments that support economic growth while maintaining environmental sustainability and social welfare.